The dynamical state of Abell 2399: a bullet-like cluster. Issue 1 (18th August 2020) - Lourenço, Ana C C; Lopes, P A A; Laganá, T F; Nascimento, R S; Machado, R E G; Moura, M T; Jaffé, Y L; Ribeiro, A L; Vulcani, B; Moretti, A; Riguccini, L A
ABSTRACT: While there are many ways to identify substructures in galaxy clusters using different wavelengths, each technique has its own caveat. In this paper, we conduct a detailed substructure search and dynamical state characterization of Abell 2399, a galaxy cluster in the local Universe ( z ∼ 0.0579), by performing a multiwavelength analysis and testing the results through hydrodynamical simulations. In particular, we apply a Gaussian mixture model to the spectroscopic data from SDSS, WINGS, and OmegaWINGS Surveys to identify substructures. We further use public XMM–Newton data to investigate the intracluster medium (ICM) thermal properties, creating temperature, metallicity, entropy, and pressure maps. Finally, we run hydrodynamical simulations to constrain the merger stage of this system. The ICM is very asymmetrical and has regions of temperature and pressure enhancement that evidence a recent merging process. The optical substructure analysis retrieves the two main X-ray concentrations. The temperature, entropy, and pressure are smaller in the secondary clump than in the main clump. On the other hand, its metallicity is considerably higher. This result can be explained by the scenario found by the hydrodynamical simulations where the secondary clump passed very near to the centre of the main cluster possibly causing the galaxies of that region to release more metals through the increase of ram-pressure stripping.